1956
DOI: 10.1017/s0007485300037123
|View full text |Cite
|
Sign up to set email alerts
|

The Leucoptera Leaf Miners of Coffee on Kilimanjaro. II.—Leucoptera caffeina Wshbn.

Abstract: A description is given of the bionomics of Leucoptera caffeina Wshbn. in the Kilimanjaro District, Tanganyika, and of the characters that distinguish it in its various stages from L. coffeella (Guér.), together with the results of population studies of the former insect and its parasites in both shaded and unshaded coffee in 1938–40.During the 1939 outbreak, the numbers of eggs per tree, and the number of live pupae present in samples of about 100 cocoons (estimated from te number of moths and parasites emergi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0
1

Year Published

1993
1993
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 2 publications
1
5
0
1
Order By: Relevance
“…Our characterization of the parasitoid community revealed that the coffee blotch miner was mostly attacked by parasitoids from the hymenopteran families Encyrtidae, Eulophidae and Braconidae. The dominance of these families reflects the findings of classic investigations on the parasitoids of coffee blotch miners in Kenya and other parts of Africa (Kerrich, 1969; Notley, 1956), as well as a more recent characterization of the parasitoid community at coffee research stations in Ethiopia (Mendesil et al, 2011). Interestingly, the impact of management intensity on the parasitoid community differed among parasitoid families, with a notable drop in the relative abundance of eulophid parasitoids in the plantation system.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…Our characterization of the parasitoid community revealed that the coffee blotch miner was mostly attacked by parasitoids from the hymenopteran families Encyrtidae, Eulophidae and Braconidae. The dominance of these families reflects the findings of classic investigations on the parasitoids of coffee blotch miners in Kenya and other parts of Africa (Kerrich, 1969; Notley, 1956), as well as a more recent characterization of the parasitoid community at coffee research stations in Ethiopia (Mendesil et al, 2011). Interestingly, the impact of management intensity on the parasitoid community differed among parasitoid families, with a notable drop in the relative abundance of eulophid parasitoids in the plantation system.…”
Section: Discussionsupporting
confidence: 64%
“…In other countries where the related leaf miner species L. coffeella is the main challenge, predatory wasps, ants, birds and bats are reported to predate on L. coffeella (Androcioli et al, 2018; De la Mora et al, 2008; Fernandes et al, 2010; Librán‐Embid et al, 2017). While the parasitoid community of the coffee blotch miner has been described in detail from plantations in other African countries (Godfray & Hassell, 1989; Notley, 1956), few studies have been carried out in Ethiopia (Mendesil et al, 2011), and none across a broader gradient of coffee management, to assess the potential for natural pest control of the coffee blotch miner in the center of the crop's origin in southwestern Ethiopia. The blotch miner is native from eastern Africa, is specialized on plants in the genus Coffea and a few other plant species, and has a particularly high density on Arabica coffee (Notley, 1956; Washbourn, 1940).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Nevertheless, the loss in production is mainly due to leaf loss (Crowe, 1964), provoked by the increase in the level of ethylene (Souza et al, 1998), principally when the lesions are near the petiole (Notley, 1956). …”
Section: Damage To the Plantsmentioning
confidence: 99%
“…(Tabela 1), observando-se diferenças estatísticas entre as temperaturas, fato também observado por Parra (1985) e Notley (1956). Magalhães et al (2012) …”
Section: Fase De Ovounclassified